PERANCANGAN CORPORATE IDENTITY S1 DESAIN KOMUNIKASI VISUAL STIKOM SURABAYA SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Pahlevi, Achmad Reza; Bahruddin, Muh; Dewanto, Thomas Hanandry (Jurnal ArtNouveau, 2014)
Enthusiast of the public withÂ  Visual Communication Design increase nowadays especially on high schooler students. In Indonesia itself having many of private universiies than nation universitie that the private universites make the same study program visual communication design. With the result now having competition beetwen private universities in each region. DKV STIKOM Surabaya is one of private universities on Surabaya. In Surabaya itself has many private universities and many of them have an identity. DKV STIKOM Surabaya not well known too with high schooler in Surabaya, so it must take action to make awareness on highschooler. The objective of this research is to find out how to create Corporate Identity that can increase brand awareness of DKV Stikom Surabaya.. The research using qualitative method, with technique observation, interviews, exsisting studies and competitor studies to get the data. After the data analysized, result the keyword of the research is âfuture creativityâ.